A state-of-the-art review of the application of phase change materials (PCM) in Mobilized-Thermal Energy Storage (M-TES) for recovering low-temperature industrial waste heat (IWH) for distributed heat supply. (May 2021) - Du, Kun; Calautit, John; Eames, Philip; Wu, Yupeng
Abstract: Mobilized-Thermal Energy Storage (M-TES) systems, are an attractive alternative solution to supply heat to distributed heat users by recovering and transporting the low-temperature industrial waste heat (IWH) by vehicular means, have the potential to reduce both the CO2 emissions and costs of energy consumption and lead to more efficient industrial activities as well as improve the quantity of low-carbon energy consumed for heat generation in the residential sector. This paper provides a state-of-the-art review of Phase Change Materials (PCM) applied in M-TES systems. The concept of the M-TES system is briefly described and summarized, including available IWH sources, heating and cooling facilities (for distributed end users), and the main features of two different types of M-TES containers. Recent research achievements in the field have been reviewed, focusing on developed prototypes, experimental and numerical studies, and economic and environmental evaluations. Finally, the barriers to the application of M-TES and possible solutions are discussed. The review highlighted that direct-contact M-TES storage systems can have up to 60% shorter charging and discharging periods when compared to indirect-contact M-TES storage systems with similar storage capacities. Using heat transfer enhancement techniques such as graphite additives, the charging and discharging period for indirect-contact M-TES container can be shortened by up to 74% and 67%, respectively, and that the charging time of direct-contact M-TES can be reduced by up to 29%. The use of M-TES to provide heat can significantly decrease the primary energy requirement, exergy losses and the CO2 emissions by up to 95%, 60% and 93%, respectively, compared to conventional heating facilities using fossil fuels. Recommendations for future research are presented, providing insights of where the current research in the M-TES field is heading and highlights the key challenges that remain to be resolved. Highlights: Mobilized thermal energy storage can be used to recover and store industry waste heat. Erythritol has been widely used as PCM for the mobilized thermal energy storage. The direct-contact system has shorter charging/discharging period than the indirect system. The price for mobilized thermal energy storage increases with the increased transport distance.